Sports injury surveillance in Japanese junior and senior high school students - Okuwaki, T. (Sports injuries and prevention, 2015)
The number and rate of sports-related injuries in junior and senior high school sports clubs were investigated for 11 sports, including soccer, using the records of the Injury and Accident Mutual Aid Benefit System from 2009 through 2011. The number and rate of sports-related injuries has increased in each sport. More than 500 cases of sports-related head and neck injuries were reported each year. Of the sports surveyed, , anterior cruciate ligament injuries were one of the most common sports-related injuries, occurred more frequently in women than in men, and were most frequent in basketball players. Establishment of a Sports Injury Surveillance system based on the Injury and Accident Mutual Aid Benefit System will be invaluable for the prevention of sports-related injuries in athletes, including junior and senior high-school students.